Anti-Trichophyton Activity of Protocatechuates and Their Synergism with Fluconazole - Soares, Luciana Arantes [UNESP]; Gullo, Fernanda Patricia [UNESP]; Orlandi Sardi, Janaina de Cassia [UNESP]; Pitangui, Nayla de Souza [UNESP]; Costa-Orlandi, Caroline Barcelos [UNESP]; Sangalli-Leite, Fernanda [UNESP]; Scorzoni, Liliana [UNESP]; Regasini, Luis Octavio [UNESP]; Petronio, Maicon Segalla [UNESP]; Souza, Patricia Fernanda [UNESP]; Siqueira Silva, Dulce Helena [UNESP]; Mendes-Giannini, Maria José Soares [UNESP]; et al. (Hindawi Publishing Corporation, 2014)
Dermatophytosis and superficial mycosis are a major global public health problem that affects 20-25% of the world's population. The increase in fungal resistance to the commercially available antifungal agents, in conjunction with the limited spectrum of action of such drugs, emphasises the need to develop new antifungal agents. Natural products are attractive prototypes for antifungal agents due to their broad spectrum of biological activities. This study aimed to verify the antifungal activity of protocatechuic acid, 3,4-diacetoxybenzoic, and fourteen alkyl protocatechuates (3,4-dihydroxybenzoates) against Trichophyton rubrum and Trichophyton mentagrophytes and to further assess their activities when combined with fluconazole. Susceptibility and synergism assays were conducted as described in M38-A2 (CLSI), with modifications. Three strains of Trichophyton rubrum and three strains of Trichophyton mentagrophytes were used in this work. The pentyl, hexyl, heptyl, octyl, nonyl, and decyl protocatechuates showed great fungicidal effects, with minimum inhibitory concentration (MIC) values ranging from 0.97 to 7.8 mg/L. Heptyl showed a synergistic activity (FIC index = 0.49), reducing the MIC of fluconazole by fourfold. All substances tested were safe, especially the hexyl, heptyl, octyl, and nonyl compounds, all of which showed a high selectivity index, particularly in combination with fluconazole. These ester associations with fluconazole may represent a promising source of prototypes in the search for anti-Trichophyton therapeutic agents.